2022
DOI: 10.3390/biomedicines10071658
|View full text |Cite
|
Sign up to set email alerts
|

Association between Polymorphisms in CFH, ARMS2, CFI, and C3 Genes and Response to Anti-VEGF Treatment in Neovascular Age-Related Macular Degeneration

Abstract: Neovascular age-related macular degeneration (nAMD) is the leading cause of vision loss in the elderly. The gold standard of nAMD treatment is intravitreal injections of vascular endothelial growth factor (VEGF) inhibitors. Genetic factors may influence the response to anti-VEGF therapy and result in a high degree of response variability. The aim of the study was to evaluate the association of the polymorphisms in genes related to the complement system (rs2285714-CFI, rs10490924-ARMS2, rs2230199-C3, rs800292-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…The CFH gene may influence treatment outcomes in patients with AMD [ 139 ], proving to be much less effective in Y402H AMD patients treated with anti-VEGF and suggesting that the mutation may be a useful predictor of treatment response; additionally, rs1065489 and rs800292 influence treatment outcomes after anti-VEGF [ 140 ]. Similarly to CFH, CFI rs2285714 is shown to respond worse to antiangiogenic treatment [ 141 ]. ARMS2 A69S is a prognostic factor for an anti-VEGF response in wet AMD in the East Asian population, but not in the Caucasian or Middle Eastern group [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CFH gene may influence treatment outcomes in patients with AMD [ 139 ], proving to be much less effective in Y402H AMD patients treated with anti-VEGF and suggesting that the mutation may be a useful predictor of treatment response; additionally, rs1065489 and rs800292 influence treatment outcomes after anti-VEGF [ 140 ]. Similarly to CFH, CFI rs2285714 is shown to respond worse to antiangiogenic treatment [ 141 ]. ARMS2 A69S is a prognostic factor for an anti-VEGF response in wet AMD in the East Asian population, but not in the Caucasian or Middle Eastern group [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is emerging evidence that a patient’s underlying genetic predisposition may affect response to existing anti-VEGF therapies. Lower risk genotypes of the VEGFA, CFH, ARMS2 and HTRA1 genes may be associated with better visual outcomes and potentially fewer injections [ 98 101 ]. Some of these genotypes were associated with poor response to one, but better response to a different anti-VEGF agent [ 102 ].…”
Section: Current Managementmentioning
confidence: 99%
“…Variability in therapeutic response may be due to hereditary factors such as genetic polymorphism. Indeed, the studies indicate that in patients with nAMD, the response to anti-VEGF therapy depends on the genotype of genes in the complement system [6,[8][9][10][11][12] and VEGF-related pathway [6,[13][14][15]. Recently, Paterno et al [16] found that single nucleotide polymorphisms (SNPs) of autophagy genes have been associated with nAMD and the outcomes of anti-VEGF treatment in a cohort of Finnish patients.…”
Section: Introductionmentioning
confidence: 99%